Boardroom diversity and carbon emissions: evidence from the UK firms - Khatri, Ishwar (Journal of business ethics, 2024)
This study provides comprehensive evidence on the link between boardroom diversity and reduction of carbon emissions. Analyzing data from a sample of 344 UK-listed non-financial and unregulated firms over the period from 2005 to 2021, our findings indicate that task-oriented (i.e., tenure) and structural (i.e., insider/outsider) board diversity are important for reducing corporate carbon emissions while relational diversity does not appear to be useful. Furthermore, the study explores the role of external carbon governance, such as the Paris Agreement, on firms with weaker internal governance structures. The findings reveal that external governance plays a critical role in curbing emissions when internal governance is not effective. Overall, our research offers valuable insights for management and regulatory bodies on the interplay between various governance mechanisms internal and external to a firm. This knowledge could guide them in determining the right mix and degree of diversity in the boardroom to achieve environmental goals.